Opioid prescriptions among the World Trade Center Health Program population - Ruiling Liu; Geoffrey M. Calvert; Kristi R. Anderson; Helen Malcolm; Lauren Cimineri; Hannah Dupont; Marisol Martinez (BMC, 2023)
Abstract Background The World Trade Center Health Program (Program) provides limited health care to those directly affected by the 9/11 terrorist attacks. Because of physical/mental trauma arising from the 9/11 attacks, Program members might be at high risk of opioid use. To prevent prescription opioid overuse, in 2018 the Program implemented various measures to improve opioid prescribing and expand access to non-opioid pain management among Program members. However, the characteristics of opioid prescriptions dispensed among this population has never been described. Methods Administrative and claims data from 07/01/2011 to 09/30/2022 were used to describe opioid prescriptions dispensed during 2013-2021. Results From 2013-2021, 108,285 members were Program-enrolled for ≥ 10 months, 4,053 (3.7%) had 22,938 outpatient opioid prescriptions, of which, 62.1% were for cancer-related pain, 11.1% for hospice/end of life care, 4.8% for surgery pain, and 9.8% for acute/chronic pain. Among members with Program-paid diagnostic/treatment claims (n = 70,721), the proportion with opioid prescriptions for cancer/hospice/end of life care increased from 0.5% in 2013 to 1.6% in 2018 (p = 0.010), then decreased to 1.1% in 2021 (p = 0.070), and the proportion for non-cancer surgery/acute/chronic pain decreased from 0.6% in 2013 to 0.23% in 2021 (p = 0.0005). Among members prescribed opioids without cancer/hospice/sickle cell disease, the proportion who started with long-acting opioids or had opioid prescriptions from ≥ 4 prescribers were below 6.5% annually; the proportion receiving a high-dose (≥ 90 morphine milligram equivalents per day [MED]), or with concurrent opioids and benzodiazepines use, or who started opioids with MED ≥ 50 or with long duration (≥ 7 days' supply) were above 10% annually, but decreased since 2017. Conclusions Prevalence of outpatient opioid prescriptions paid by the Program was very low and prescriptions were primarily dispensed for cancer/hospice/end of life care. Although Program efforts to improve opioid prescribing coincided with improvements in outcomes, ongoing surveillance is needed.